Product market competition and efficiency of corporate tax management. Issue 2 (7th May 2019) - Wang, Tina
Abstract : Purpose: The purpose of this paper is to test the economic theory that product market competition should enhance firm performance in the US corporate tax management setting. It identifies one mechanism through which corporate management can improve firm performance. The paper also identifies business conditions that may facility or impede effective corporate tax management. Design/methodology/approach: The paper tests the relationship between product market competition and corporate tax efficiency using large archival data. The primary data source is COMPUSTAT, which contains annual and quarterly accounting data for US public firms. Other data sources include accounting comparability data generously shared by Professor Vedi. Findings: The paper finds that firms in competitive industries are more efficient in managing taxes. Specifically, the paper documents that firms in competitive industries exhibit lower effective tax rates than their non-competitive counterparts. Furthermore, the paper finds that the positive link between competition and the efficiency of tax management is much stronger for firms with lower cash flow volatility and for firms with fewer industry investment opportunities. The lack of financial statement comparability may weaken this link. Research limitations/implications: Tax laws vary greatly from country to country. Readers should interpret the results within the US tax environments. Practical implications: Results in this paper have implications for multinational corporations that are interested in investing and doing business in the USA. Originality/value: This paper sheds light on how competition influences firm performance through efficient tax management, a specific mechanism through which competition improves firm performance. To the best of the author's knowledge, this study provides the first documentation of how product market competition affects tax planning for US publicly traded companies.